Synthesis of jet fuel range high-density polycycloalkanes with vanillin and cyclohexanone. Issue 6 (25th February 2022) - Gao, Haofei; Han, Fengan; Li, Guangyi; Wang, Aiqin; Cong, Yu; Li, Zhizhou; Wang, Wei; Li, Ning
Abstract : Diesel and jet fuel range C13 polycycloalkanes were first synthesized with vanillin and cyclohexanone, two platform compounds which can be derived from lignin. Abstract : In this work, jet fuel range high-density polycycloalkanes, dicyclohexylmethane and dodecahydrofluorene, were first synthesized by a two-step method with vanillin and cyclohexanone, two platform compounds that can be derived from lignin. In the first step, 2-(4-hydroxy-3-methoxybenzylidene)cyclohexan-1-one, a jet fuel range C13 polycycloalkane precursor, was obtained through an acid-catalyzed aldol condensation reaction between vanillin and cyclohexanone over a series of titanium dioxide based nanometer material catalysts. Among them, sulfated titania nanofibers (STNFs) exhibited the highest activity. Over them, a high yield (81%) of 2-(4-hydroxy-3-methoxybenzylidene)cyclohexan-1-one was obtained after the reaction was carried out at 423 K for 10 h. On the basis of the characterization results, the good performance of the STNF catalyst can be attributed to its higher acid strength and higher Brønsted to Lewis acid site ratio. Subsequently, the aldol condensation product was further converted to a mixture of dicyclohexylmethane and dodecahydrofluorene by hydrodeoxygenation (HDO) under the co-catalysis of Pd/C and H-Y zeolite. According to our measurement, the cycloalkane mixture as obtained from the HDO process has a higher density (0.95 g mL −1 ) and lower freezing point (256 K). As a potential application, it can be blended into low freezing point jet fuels to improve their volumetric heat values.